The Role of Technology in Monitoring Land Pollution in Indonesia - Khoirunisa, Aisha Putri; Husein, Risha Khaitunnisa; Ramadhan, Syaldila Diffa; Ardiansyah, Gamal Muhammad Adam; Zalni, M. Ilham Kumala; Situmorang, Marningot Tua Natalis; Hanaseta, Evelyn (Golden Ratio of Data in Summary, 2025)
Soil pollution in Indonesia has become a serious environmental issue caused by industrial activities, intensive agriculture, and domestic waste. Technology plays a crucial role in detecting, monitoring, and managing soil contamination more effectively and efficiently. This paper discusses the application of various technologies such as the Internet of Things (IoT), environmental sensors, and Geographic Information Systems (GIS) in monitoring soil pollution in Indonesia, including the benefits, challenges, and implementation recommendations.